Comparison of Cerebrospinal Fluid Amyloidogenic Nanoplaques With Core Biomarkers of Alzheimer’s Disease - Aksnes, Mari; Tiiman, Ann; Edwin, Trine Holt; Terenius, Lars; Bogdanović, Nenad; Vukojević, Vladana; Knapskog, Anne-Brita (Frontiers in Aging Neuroscience, 2021)
Accurate biomarkers of Alzheimer’s disease (AD) are essential for early diagnosis and intervention. Available biomarkers are not sufficient to permit the monitoring of AD progression over time, and additional biomarkers are required. Measures of aggregated amyloid-β (Aβ) could be useful biomarkers for AD. Here, we investigate whether levels of Thioflavin-T (ThT) positive amyloid aggregates, i.e., nanoplaques, in cerebrospinal fluid (CSF) could serve as useful biomarkers for AD. One-hundred and eighteen memory clinic patients were AT(N) classified, and CSF nanoplaque concentrations were compared between patients on the “Alzheimer’s continuum” (A+ patients) and patients with “Normal AD biomarkers” or “Non-AD pathologic change” (A− patients). CSF nanoplaque concentrations and sizes were quantified using the novel ThT-Fluorescence Correlation Spectroscopy (ThT-FCS) assay, and core biomarkers (Aβ42, total tau and phosphorylated tau) were determined by enzyme-linked immunosorbent assays. We investigated the association between nanoplaque concentrations and core biomarkers, and the diagnostic value of nanoplaque levels. Nanoplaque levels were increased in A+ patients compared to A− patients. Nanoplaque concentrations were negatively associated with Aβ42, but not related to total tau or phosphorylated tau measures. Quantification of nanoplaques did not improve the classification of patients on the Alzheimer’s continuum compared to the core biomarkers alone. Dynamic changes in nanoplaques concentration and size throughout AD stages should be explored in longitudinal studies.